Praktik Objektifikasi Seksual Tubuh Perempuan dalam Komentar Tiktok: Analisis Isi Interaksi Antar perempuan - Intan Puspita Sari; Anang Masduki (Jurnal Ragam Pengabdian, 2026)
The development of visual-based social media such as TikTok has created digital interaction spaces where responses to women’s bodies frequently appear in the comment section. This study aims to analyze the practice of sexual objectification of women’s bodies in TikTok comments among female users using Objectification Theory and the concept of the male gaze. This research employs a qualitative approach using qualitative content analysis of 60 comments written by female users on five TikTok videos uploaded during December 2025–February 2026. The findings show that objectification appears through direct focus on body parts, euphemistic expressions, imagined bodily intimacy, sexual humor, and compliments containing sexualization. Interactions among female users also reproduce internalized male gaze, which normalizes objectification within digital conversations